Enhanced allergic sensitisation related to parental smoking. Issue 4 (April 1992) - Ronchetti, R; Bonci, E; Cutrera, R; De Castro, G; Indinnimeo, L; Midulla, F; Tancredi, G; Martinez, F D
Abstract : The objective of this study was to assess the role of parental smoking in changes, after a four year interval (1983-7), in the prevalence and severity of the atopic state in 166 pre-adolescent children. Allergy skin prick tests were related to parental smoking habits and their changes during this same interval. The total number of cigarettes smoked by parents decreased in 56 families while it increased in only 16. Boys had significantly more persistently positive skin tests and changed more frequently from negative to positive. The skin test index did not show significant changes in girls. This index did not change in children of persistent non-smokers or those starting to smoke during this period, while it increased among sons of those that quit smoking and of persistent smokers. This was not only due to those boys who became skin test positive during follow up. When analysis was restricted to 14 boys who had been skin test positive in 1983 and whose parents were persistent smokers, the index increased in eight, remained unchanged in four, and decreased in only two. This report supports the hypothesis that parental smoking is a factor that, together with specific allergenic exposure, may enhance allergic sensitisation in children.